Kulanjan (alpinia galanga) from the perspective of unani medicine - Shiffa, M.S.M.; Fahamiya, N.; Farzana, M.U.Z.N.; Miriyalini, P. (International Journal of Universal Pharmacy and Bio Sciences, 2016)
Kulanjan (Alpinia galanga) is a rhizomatous perennial herb used in traditional systems of medicine especially in Unani medicine. It is used as a single drug or as a compound medicine and it has actions such as expectorant, nerve stimulant, digestive, appetizer, stomachic, cardiac tonic, carminative, etc. The aim of this study is to gather relevant data regarding Kulanjan in order to give base for the researchers for further studies. The rhizome is generally used as a spice or as a source of essential oil. The flowers and young shoots are used as vegetables or as spices. It contains flavonoids and volatile oils. Actions and uses of Kulanjan have been mentioned in many places of authentic Unani classical text books such as Al Qanun-fil-tibb, Magzanul mufradat, Bisthanul mufradat, etc. In addition to that Siddha materia medica, Ayurveda pharmacopoeia and many other traditional books have also mentioned its actions and uses clearly. Further, there are hundreds of authentic scientific articles which have scientifically proved its beneficial actions in various diseases through many research studies. When critically reviewed these articles, it is revealed that this herb possessed many pharmacological activities such as antitumorgenic, antioxidant, anti-inflammatory, hepatoprotective, diuretic, antibacterial, antifungal, antiviral, antiprotozoal, immunomodulatory, antidiabetic, antiplatelet, hypolipidemic, anti-oxidant antipyretic and, many other pharmacological properties. Further this herb can be used to treat several diseases like arthritis, cancer, asthma, sinusitis, infections etc. Therefore, randomized controlled clinical studies should be undertaken to reveal all its medicinal potential in order to utilize the maximum benefit of this herb.
Keywords: Kulanjan; Herbal medicine; Unani Medicine; Alpinia galanga